X-ray imaging: Reaching the third dimension - Robinson, Ian; Huang, Xiaojing (Nature materials, 2017)
X-ray imaging in three dimensions is now possible from a set of 2D coherent Bragg diraction patterns. This approach overcomes the necessity of having to rotate the sample for a 3D reconstruction. X-ray imaging is extensively usedin medical and materials science. Traditionally, the depth dimension is obtained by turning the sample to gain dierent views. The famous penetrating properties of X-rays mean that projection views of the subject sample can be readily obtained in the linear absorption regime. 180 degrees of projections can then be combined using computed tomography (CT) methods to obtain a full 3D image,a technique extensively used in medical imaging. In the work now presented in Nature Materials, Stephan Hruszkewycz and colleagues have demonstrated genuine 3D imaging by a new method called 3D Bragg projection ptychography1. This approach combines the side view capability ofusing Bragg diraction from a crystalline sample with the coherence capabilities of ptychography. It therefore results in a 3D image from a 2D raster scan of a coherent beam across a sample that does not have to be rotated.